The Effect of Sports Extracurricular Participation on Confidence and Social Interaction of High School Students - Aziz, Muhammad Ivan Miftahul; Jahrir, Andi Sahrul (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the influence of sports extracurricular participation on students' confidence and social interaction at SMA Karika Chandra Kirana Makassar. Participation in sports and extracurricular activities is believed to have a positive impact on students' psychosocial development. This study uses a quantitative design with an ex post facto approach. The research sample consisted of 63 students who actively participated in the sports of football (21 students), basketball (15 students), volleyball (12 students), karate (7 students), and badminton (8 students), who were selected using purposive sampling techniques. The instruments used included sports extracurricular participation questionnaires, The Self-Confidence Scale, and the Social Interaction Scale. The results of regression analysis showed that sports extracurricular participation had a significant effect on these two psychosocial variables. The regression model for the effect of participation on self-confidence showed an R Square value of 0.919 with a t-value of 26.33 and a Sig. of 0.000. As for the effect of participation on social interaction, the R Square value was 0.934 with a t value of 29.39 and Sig. 0.000. Based on these results, it can be concluded that sports extracurricular participation plays an important role in increasing students' confidence and social interaction skills. Schools should encourage student participation in sports activities as part of their psychosocial development efforts.